Pemaknaan Korban Kekerasan Seksual (Analisis Resepsi Audiens Terhadap Film 27 Steps of May) - Balqis, Maulida; Samatan, Nuriyati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2021)
Sexual violence against women seems to be a never ending crime. Every year, this case continues to experience a fairly sharp increase. Various groups ranging from ordinary people, activists, to institutions such as Komnas Perempuan tried to highlight and make people aware of the urgency of this case. 27 Steps of May is one of the films that voices the case of sexual violence against women. Through the film, the filmmakers tried to convey social criticism of the dangers of the impact of this case. The purpose of this study is to determine the audience's interpretation of the message about victims of sexual violence in the 27 Steps of May film. This study uses a qualitative approach with reception analysis method. The results show that most of the audience interpret the message in the 27 Steps of May film very well and appropriately. However, there are also audiences who have different views in interpreting it. Of the eight analytical units studied, three of them are accepted by the audience in a negotiating position, one unit places an informant in an opposition position, and other units are accepted by all informants in a dominant hegemonic position.